Navigating Minority & Gender Discrimination, Substance Use Disorder, Financial Distress & Workplace Politics: Lessons For Work-Life Wellness in Academic Medicine: Part 2 of 3: Wellness in Academic Medicine - Ahmed, Rami; Hartwell, Jennifer; Farley, Heather; MacRae, Julia; Rogers, David; Lawrence, Elizabeth; Brazeau, Chantal; Park, Eliza; Cassidy, Anna; Hartsock, Jane; Holmes, Emily; Schroeder, Kristen; et al. (Kansas Journal of Medicine, 2023)
In this second of three manuscripts addressing a range of complex work and personal issues, the authors explore case scenarios with characters who work in the fields of general surgery, orthopedic surgery, anesthesiology, neurology, radiology, and otolaryngology. The medical specialty identifiers help inform some baseline understanding of the demands of that particular profession but are less pertinent than the specifics of each case. In this manuscript, the authors dive into the topics of navigating a lawsuit and professional burnout, personal finances, substance use disorder, demands of clinical work and workplace politics, diversity and inclusion, and dealing with major personal illness. The authors provide practical steps to help the readers deal with similar situations and provide insight to support persons on how to improve support structures.